###### Advertisements

###### Advertisements

Sum

Evaluate (x^{5}) × (3x^{2}) × (-2x) for x = 1.

###### Advertisements

#### Solution

For x = 1

(x^{5}) × (3x^{2}) × (−2x)

(1^{5}) × (3 × 1^{2}) × (−2 × 1)

1 × 3 × (−2)

= −6

Concept: Multiplying a Polynomial by a Polynomial

Is there an error in this question or solution?

#### APPEARS IN

#### RELATED QUESTIONS

**Multiply:** 6x^{3} − 5x + 10 by 4 − 3x^{2}

**Multiply: **2y − 4y^{3} + 6y^{5} by y^{2} + y − 3

**Multiply:** 5p^{2 }+ 25pq + 4q^{2} by 2p^{2} − 2pq +3q^{2}

**Simplify : **(4x – 5y) (5x – 4y)

The adjacent sides of a rectangle are x^{2} – 4xy + 7y^{2} and x^{3} – 5xy^{2}. Find its area.

The base and the altitude of a triangle are (3x – 4y) and (6x + 5y) respectively. Find its area.

Evaluate (3x^{4}y^{2}) (2x^{2}y^{3}) for x = 1 and y = 2.

If x = 2 and y = 1; find the value of (−4x^{2}y^{3}) × (−5x^{2}y^{5}).

**Evaluate: **(3x – 2)(x + 5) for x = 2.

**Evaluate: **(2x – 5y)(2x + 3y) for x = 2 and y = 3.